(untitled) (Mutah Journal of Humanities and Social Sciences (MJHSS), 2025)
The study aimed to identify the impact of crisis management strategies on the performance of employees in industrial companies listed on the Amman Stock Exchange. To achieve the study objectives, the descriptive analytical approach was used based on the study tool (questionnaire) to collect data, which was developed after referring to previous studies. The study population consisted of all employees at administrative levels in industrial companies listed on the Amman Stock Exchange, totaling (340) employees. The questionnaire was distributed to a facilitated random sample consisting of (220) employees from the study population. The Statistical Package for Social Sciences (SPSS, 27) was used. This shoes that there is a significant degree in the impact of crisis management strategies on employee performance in industrial companies, with a slight difference, as the work team strategy has a greater impact on employee performance, followed by the change-of-course strategy, followed by the crisis fragmentation strategy, followed by the crisis containment strategy. Among the most important recommendations of the study are: the necessity of leveraging the exchange of expertise among employees in crisis management, and the need to form sector-wide task forces to foster creative ideas among employees for addressing the crises facing Jordan’s industrial sector.